Emotions in Wikipedia: the role of intended negative events in the expression of sadness and anger in online peer production. Issue 8 (3rd August 2019) - Greving, Hannah; Kimmerle, Joachim; Oeberst, Aileen; Cress, Ulrike
ABSTRACT: The online encyclopaedia Wikipedia has strict guidelines for ensuring the objectivity of its content and unbiased language of its articles. Wikipedia also provides articles on negative events such as disasters. Depending on the event, the Wikipedia community may express certain emotions when writing Wikipedia articles on those events. So far, it is unclear which psychological mechanisms are reflected in the potential emotional expressions. Based on appraisal theories of specific emotions and on previous research on intentional harm, we investigated whether intentional negative events such as terrorist attacks elicited different emotional expressions than unintentional negative events, such as natural or man-made disasters. We analysed N = 330 Wikipedia articles with automatic linguistic text analyses and found that Wikipedia articles on man-made attacks (e.g. terrorist attacks, shooting rampages) contained more anger-related content than Wikipedia articles on man-made disasters (e.g. ship accidents, train accidents) and natural disasters (e.g. hurricanes, flooding); F (2, 327) = 127.78, p < .001, η p 2 = .439. Wikipedia articles on man-made attacks also contained fewer sadness-related words than articles on natural and man-made disasters, F (2, 327) = 19.01, p < .001, η p 2 = .104. We discuss the implications of these findings with respect to theory and practical applications.